Social representations of a group of ex-combatants on compliance with the Peace Agreement - Pérez Gamboa, Alfredo Javier; Sánchez Castillo, Verenice; Gómez Cano, Carlos Alberto; Pérez Gamboa, Alfredo Javier; Sánchez Castillo, Verenice; Gómez Cano, Carlos Alberto; Pérez Gamboa, Alfredo Javier; Sánchez Castillo, Verenice; Gómez Cano, Carlos Alberto (Corporación Universitaria Americana, 2023)
Introduction: the peace process in Colombia, the signing of the Havana Treaty and its compliance, have been the subject of various investigations. Due to the long history of the conflict and the multiple attempts at pacification, the Peace Treaty represented an important opportunity to resolve deep-rooted social problems in the affected territories. Objective: the objective of the study was to describe the social representations of ex-combatants about the Peace Treaty. Methodology: a basic qualitative design based on observation, interview and triangulation of sources was implemented. Results: the main results point towards a social representation of variable polarity according to the specific points, the predominance of ideas and beliefs related to the construction of the future, a favorable appreciation of the transition and resistance related to the historical problems that generate the conflict. Conclusions: it is concluded that the representation of ex-combatants is marked by the idea that peace, as was the armed conflict, is a process that entails advances and setbacks.